Risk factor frequencies in ischemic and hemorrhagic stroke: - Musavi Lotfi, S.M; Lotfi, R; Dadkhahi Tehrani, T; Abedini, Z; Khorami, A (Advances in Nursing & Midwifery, 2009)
Background Stroke is the most common neurologic disorder and the third leading cause of death in many countries. It has two types: ischemic and hemorrhagic. The latter has more complications and is lethal. Some risk factors of stroke include diabetes, hypertension, smoking and hyperlipidemia. Purpose This cross-sectional study was conducted to compare the frequencies of risk factors in patients with ischemic and hemorrhagic stroke, hospitalized at Hazrat-e-Rasoul Hospital in 2007. Methods 100 patients were randomly selected in an every other manner for each type of stroke and assessed as well as compared in terms of most significant risk factors. A form for recording age, sex, type of stroke and related risk factors was used to collect data from medical records. Results 74% and 26% of the patients suffered from ischemic and hemorrhagic stroke respectively. Mean ages of the first and second group were 68.3±16.56 and 61.9±13.69. The frequencies of risk factor in ischemic stroke were 64.86% for diabetes, 56.75% for hypertension, 21.62% for smoking and 13.51% for hyperlipidemia. The corresponding figures for hemorrhagic stroke were 65.38%, 61.53%, 3.8% and 3.8%. A significant difference was found between the frequencies of smoking (P=0.048) and hyperlipidemia (P=0.000) in ischemic and hemorrhagic stroke. Conclusion With respect to high frequencies of the above risk factors, controlling them in a better and more accurate manner, increasing public awareness and modifying life style are valuable in primary and secondary prevention of stroke and its complications. Keywords: Stroke, Ischemic stroke, Hemorrhagic stroke, Risk factors, Diabetes, Hypertension, Smoking, Hyperlipidemia.